Pemanfaatan Limbah Kulit Jeruk Bali sebagai Inovasi Produk Lokal UMKM - Evani Chilvi Almaisyaroh; Atiatu Kiky Lu’lu’a; Ronaldo Maria Pereira Alves; Lyvia Zahrani; Reza Johan Tribuana; Anita Zulfiani (Ilin Institute, 2026)
Pomelo peels waste in Klampisan Village, which has not been optimally utilized, has the potential to be processed into high value products. This community service program aims to encourage the use of pomelo peels as an innovative product for small and medium enterprises while supporting community economic empowerment. The method used is a descriptive-explanatory qualitative approach through observation and participatory demonstrations conducted during the community service program on January 22, 2026, at the Klampisan Village Hall. The results show that pomelo peels can be processed into sweet and sour candies with a chewy texture and distinctive aroma. This outreach activity enhances community knowledge and skills while creating business opportunities based on local resources that are simple, affordable, and sustainable.